Tracing Thought. The Chiasm of Writing between Derrida and Nishida - Bon, Emma Lavinia (Scenari, 2024)
The purpose of this article is to investigate the plexus between writing and thinking. This goal is pursued through a comparison between the calligraphic practice of Japanese philosopher Nishida Kitarō and Jacques Derrida’s conception of écriture. Although there are some significant differences between the approaches of the two philosophers, both agree in showing how thought is produced inseparably from the bodies that express it and the written signs that convey it. The aesthetic dimension is thus inseparable from the theoretical, like the two edges of différance. The Nishidian notions of kōiteki chokkan 行為的直観 (active intuition) and narikiru 成り切る (knowing by becoming) will thus be explored through dialogue with Derridean notions of différance and écriture.